Levels and profiles of long-chain perfluoroalkyl carboxylic acids in Pacific cod from 14 sites in the North Pacific Ocean. (April 2019) - Fujii, Yukiko; Tuda, Hayato; Kato, Yoshihisa; Kimura, Osamu; Endo, Tetsuya; Harada, Kouji H.; Koizumi, Akio; Haraguchi, Koichi
Abstract: We investigated the profiles and levels of perfluoroalkyl carboxylic acid (PFCA) contamination in Pacific cod ( Gadus macrocephalus ) from the North Pacific Ocean. The mean concentrations of PFCAs containing 8 to 14 carbon atoms (C8–C14) in edible Pacific cod muscle ranged from 216 to 670 pg g −1 wet weight in the Northeast Pacific Ocean (Seattle, Vancouver, Alaska, and Russia), from 819 to 1710 pg g −1 wet weight in Japanese coastal waters (Hokkaido, Aomori, Iwate, Miyagi, Tottori, and Shimane), and from 288 to 892 pg g −1 wet weight in Korean waters (Sokcho, Busan, and Yeosu). These results indicate there are geographical differences in the distribution of PFCAs. The long-chain PFCAs (C9–C14) contributed 96% of the total PFCA concentration across Japan, whereas they contributed only 33% of the total PFCA concentration in the USA and Canada. Long-chain PFCA concentrations in cod samples collected in Japanese and Korean waters were about three to four times those in samples from the USA, Canada, and Russia. Because seafood is considered an important dietary source of PFCAs, high concentrations of long-chain PFCAs in Pacific cod from Japanese and Korean waters may affect human dietary exposure and blood concentrations of long-chain PFCAs. Graphical abstract: Image 1 Highlights: Perfluoroalkyl carboxylic acids were detected in edible muscle from North Pacific cod. PFCA profiles varied around the North Pacific regions. C11, C12, and C13 PFCA levels in East Asia were higher than those at the other sites. These high concentrations in fish may result in high dietary exposure for humans. Abstract : Long-chain PFCA concentrations in cod are high in Japan, and may be related to human serum concentrations.